Investigation of graphene oxide as reinforcement for orthopaedic applications. (March 2014) - Suñer, S.; Emami, N.
<x content-type="archive" xml:space="preserve">Abstract</x> Carbon based polymer composites have been suggested as an alternative to conventional ultra high molecular weight polyethylene (UHMWPE) in total joint replacements. The aim of this study was to investigate the use of graphene oxide (GO) as reinforcement of UHMWPE. Under optimised mixing conditions, the prepared UHMWPE/GO composite showed an enhanced thermal stability compared to conventional UHMWPE. Also, the present study has shown the potential of ball milling as a processing method for synthesising UHMWPE/GO composites to be used in load bearing implants.